OBDT-theta, a multi-channel TDC and readout board for the CMS muon drift tubes in HL-LHC - Bedoya, C. F.; Cuadrado, S.; Cuchillo, J.; Eliseev, D.; Esper, N.; Francia, D.; Navarro, A.; Paz, R.; Presser, C.; Redondo, I.; Redondo, D. D.; Sastre, J. (Frontiers in Detector Science and Technology, 2025)
A new readout board for the digitization of the CMS (Compact Muon Solenoid) Muon Drift Tube (DT) chambers has been designed in order to cope with the increase of occupancy and trigger rates expected during operation under the foreseen luminosity in the HL-LHC (High Luminosity Large Hadron Collider). The board OBDT-theta (On-detector Board for Drift Tubes) can perform the time digitization and readout of the DT chamber signals measuring the z-coordinate (along the beam axis) of CMS. A total of 228 channels can be digitized with a time bin of 0.78 ns and full streaming of all the DT chamber signals can be made through optical links into the CMS counting room. There, the full detector information can be available to perform the trigger and event building logic. The different functionality of the OBDT-theta board has been verified and the overall architecture has been validated through specific tests. The OBDT-theta architecture and main functionality will be presented in this contribution, showing the suitability of the design for the expected functionality during the HL-LHC.